Vaccination of 50+ adults to promote healthy ageing in Europe: The way forward. Issue 39 (18th September 2018) - Esposito, Susanna; Principi, Nicola; Rezza, Giovanni; Bonanni, Paolo; Gavazzi, Gaetan; Beyer, Ingo; Sulzner, Michael; Celentano, Lucia Pastore; Prymula, Roman; Rappagliosi, Andrea; Sevilla, Joseph; Poland, Gregory; et al.
Highlights: Good health is essential for active ageing. Childhood diseases are becoming diseases of the adults. A holistic approach is needed when assessing the value of vaccination. The shift from childhood to life-long vaccination is essential to promote healthy ageing. Key actions with a European multidisciplinary network to promote vaccination of 50+ appear mandatory. Abstract: The proportion of the population ≥65 years old is about 17% today and will be about 27% in 2050 worldwide. The problem, however, is not ageing in itself, it is individual disabilities associated with ageing. This manuscript summarizes the consensus points reached during a pan-European meeting on gaps and barriers in making vaccination of adults aged 50+ a reality and on further joint actions in Europe. The shift from childhood to life-long vaccination is essential to prevent disability, morbidity and mortality in the elderly and promote healthy ageing. This vaccination shift is a major challenge in the post-truth, media-based era in countries with dwindling resources for the provision of healthcare. The challenge can be met only by adopting an innovative approach designed to shift the mindset of decision-makers from treatment to prevention. A number of key actions are required and for these actions a European multidisciplinary network including health authorities, medical doctors with different specialties, sociologists, psychologists, pharmaceutical companies and Associations of patients appears mandatory.